PROPOSED CO2 HYDRATE TECHNOLOGY APPLICATION FOR CARBON CAPTURE AND STORAGE IMPLEMENTATION IN INDONESIA - Yusep Kartiwa Caryana (Scientific Contributions Oil and Gas, 2017)
Carbon Capture and Sequestration (0r Storage)—known as CCS needs to be implemented in various development activities in Indonesia including downstream oil and gas industry because the government of Indonesia has adopted the Paris Agreement on Greenhouse Gas Emissions Reduction. Various capture techniques have been developed for capturing CO2 from post combustion emission. One of the new approaches considered for capturing CO2 and hence reducing to atmospheric emissions is based on gas hydrate (crystallization) technology. The basis of the technology is the selective partition of the target component between the hydrate phase and the gaseous phase. It is expected that CO2 is preferentially trapped and encaged into the hydrate crystal phase compared to the other components. Previous study found that the gas/hydrate equilibrium pressure and temperature for the fl ue gas mixture in the range of 7.6 MPa and 11.0 MPa at 274 K and 277 K respectively, are inappropriate to the downstream oil and gas industrial reality because the operating cost will be expensive to compress the gas to the hydrate formation pressure. Suitable hydrate promoters including Tetrahydrofuran (THF) and Sodium Dodecyl Sulfate (SDS) can be used to achieve moderate hydrate formation pressure and energy consumption appropriate to the industrial reality. In the presence of THF and SDS about 62.3 Nm3/m3 CO2 hydrate can be formed at 30 bar pressure and 274 to 277 K temperature within around 15 minutes reaction time.Many experiments result indicates that continuous hydrates formation will be feasible for scale-up to industrial settings including downstream oil and gas industry emission reduction if the technology assures an optimal contact between gas and liquid phases plus the proper hydrate promoter. However, compared to current international carbon credit, the feasibility of onshore CO2 abatement cost in downstream oil and gas industry sensitively depends on the distance of CO2 hydrate pipeline transportation.